Phytochemical Screening, Antioxidant and Antiplasmodial Activities of methanol and n-hexane extracts from Stem Bark of Tectona grandis (Lamiaceae) - Nwaeze, Kenneth U.; Ayoola, Gloria O.; Anyakora, Chimezie A.; Oparah, Blessing; Chiedu, Daphnie; Shode, Francis O.; Odhav, Bharti; Smith, Peter (Nigerian Journal of Pharmaceutical and Applied Science Research, 2020)
Ciprofloxacin is a flouroquinoline antibiotic with a broad spectrum of activity used for the treatment of various bacterial infections including anthrax. The use of substandard or fake ciprofloxacin products will jeopardise their usefulness. Hence, the need for provisions of simple and cost-effective method(s) of assay that will encourage regular and quick sampling of ciprofloxacin tablets. Different brands of ciprofloxacin hydrochloride tablets purchased randomly from drug stores in the study centre, and coded A-J, were assayed for weight uniformity, friability, hardness, disintegration, dissolution rate using standard physical methods. Their percentage drug contents were determined using spectrophotometric and titrimetric methods. The spectrophotometric measurement was done at a wavelength of 276nm while the titrimetric method was based on oxidative reaction between ciprofloxacin and potassium permanganate yielding the oxide as a greyish pink colour at end point. All the brands met the requirements for weight uniformity, friability, disintegration and dissolution. Only one brand, sample E, failed the hardness test. The titrimetric and spectrophotometric assay showed that seven of the brands met the British Pharmacopoeia requirement for percentage drug content (95.0-105.0%). Statistical analysis showed no significant difference (p<0.05) between the results obtained from both the titrimetric and spectrophotometric methods. The two methods are reliable, simple and cost-effective and can be routinely used to assay ciprofloxacin tablets.